Kakadu plum in the treatment of Giardiasis - Wright, Mitchell Henry (Pharmacognosy Communications)
Giardiasis (caused by protozoal parasites of the genus Giardia) is a crip- pling gastrointestinal disease. A recent report by researchers at Griffith University, Australia has reported that extracts prepared from Termi- nalia ferdinandiana (Kakadu plum) fruits are effective in the inhibition of growth of Giardia duodenalis trophozoites.1 Fruit extracts prepared with water were particularly effective inhibitors but anti-Giardial activity was also detected in methanolic, ethyl acetate and chloroform extracts. Through these results, the authors identified several compounds likely attributing to the inhibitory activity of G. duodenalis. This study offers an innovative approach to the prevention of giardiasis and further high- lights the significance of Kakadu plum in the treatment and prevention of microbially caused diseases. This is a significant finding in the treat- ment of giardiasis as currently there are limited options from a chemo- therapeutic standpoint. The ability of the aqueous fruit extract to act as a potent inhibitor offers a natural means of treatment as preparation can be achieved without the use of a chemical solvent. Furthermore, ingestion of Kakadu plum as a natural food source may offer a means of giardiasis prevention. Finally, there have been numerous reports of G. duodenalis resistances to metronidazole (the gold standard) and other drugs2 and this paper offers an additional means of treatment. The authors suggest a ground-breaking approach to the management of giardiasis as well as present Kakadu plum as an excellent natural resource for drug devel- opment.